2020
DOI: 10.1093/infdis/jiaa116
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Neutralization of Norovirus Is Mediated by Antibodies Against the Protruding Domain of the Major Capsid Protein

Abstract: Human noroviruses are the most common viral agents of acute gastroenteritis. Recently, human intestinal enteroids were shown to be permissive for norovirus infection. We tested their suitability as a system to study norovirus neutralization. Hyperimmune sera raised against virus-like particles (VLPs) representing different genotypes showed highly specific neutralization activity against GII.4 and GII.6 noroviruses. Carbohydrate blocking assays and neutralization exhibited similar patterns in antibody responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Virus-like particles were produced as described elsewhere. [23 , 24] Wells of polystyrene microtiter-plates (BM6001; BMBIO, Tochigi, Japan) were coated with 100 µL/well of 0·5 µg/ml (GII) or 0·25 µg/ml (GI) VLPs in carbonate-bicarbonate buffer (pH 9·6). Following blocking with 5% Blotto (37530; Thermo Scientific, Massachusetts, USA), the wells were incubated with 100 µL of 1:50, 1:100, 1:500, 1:1000, 1:5000, and 1:10,000 dilutions of breast milk serum for two hours.…”
Section: Methodsmentioning
confidence: 99%
“…Virus-like particles were produced as described elsewhere. [23 , 24] Wells of polystyrene microtiter-plates (BM6001; BMBIO, Tochigi, Japan) were coated with 100 µL/well of 0·5 µg/ml (GII) or 0·25 µg/ml (GI) VLPs in carbonate-bicarbonate buffer (pH 9·6). Following blocking with 5% Blotto (37530; Thermo Scientific, Massachusetts, USA), the wells were incubated with 100 µL of 1:50, 1:100, 1:500, 1:1000, 1:5000, and 1:10,000 dilutions of breast milk serum for two hours.…”
Section: Methodsmentioning
confidence: 99%
“…35,36 Importantly, it has been recently shown that carbohydrate blockade assays and neutralization in HIE present similar patterns in antibody reactivity. 11,37 As the HIE culture system exhibits evident disadvantages, such as limited scalability to high-throughput and/or the inability of certain noroviruses to replicate in the cells, the blockade assays are a good alternative to determining the antigenic relationships between strains and to study antibody-mediated protection. 11,12,37,38 While some animal models have been developed for human noroviruses, 14,39-41 they either do not recapitulate disease or replication has been shown for only a limited number of strains.…”
Section: The Correlates Of Protection For Human Norovirusesmentioning
confidence: 99%
“…Preliminary neutralization experiments in HIE and analyses of natural reinfection cases over time suggest that some norovirus genotypes are antigenically distinct from each other. 11,17,42,[53][54][55] Despite all these studies, extensive analyses of the functional (blockade/neutralizing) antibodies between all human norovirus genotypes have not been performed.…”
Section: The Impact Of Norovirus Diversity On Immunitymentioning
confidence: 99%
See 2 more Smart Citations